2015
DOI: 10.15353/cfs-rcea.v2i1.62
|View full text |Cite
|
Sign up to set email alerts
|

From Food Mail to Nutrition North Canada: Reconsidering federal food subsidy programs for northern Ontario

Abstract: <p>This paper is a critique of the report released on 25 November 2014 by the Auditor General of Canada (AG), Michael Ferguson, on Nutrition North Canada (NNC), a subsidy program designed to lower the cost of “perishable nutritious food” in northern communities. We argue that the situation is far more complicated than the AG’s report allows and suggest that looking at the challenges faced by the provincial Norths will show the real deficits of NNC.</p><p> </p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…We included a community in our study if it met any of the following criteria: it was located in the provincial Norths, Yukon, Northwest Territories, Nunavut, Nunavik, or Labrador; it was part of the NNC program; it was included in the article "From Food Mail to Nutrition North Canada: Reconsidering Federal Food Subsidy Programs for Northern Ontario," published in Canadian Food Studies in May of 2015; 6 or, finally, it was listed on the NWC website. In northern Ontario, we also included the municipality of Moosonee because it serves as an important entry point for northern First Nations in the Mushkegowuk territories for services (food, general goods and health care) and is only accessible year-round by rail (as all-season roads are not yet operational).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included a community in our study if it met any of the following criteria: it was located in the provincial Norths, Yukon, Northwest Territories, Nunavut, Nunavik, or Labrador; it was part of the NNC program; it was included in the article "From Food Mail to Nutrition North Canada: Reconsidering Federal Food Subsidy Programs for Northern Ontario," published in Canadian Food Studies in May of 2015; 6 or, finally, it was listed on the NWC website. In northern Ontario, we also included the municipality of Moosonee because it serves as an important entry point for northern First Nations in the Mushkegowuk territories for services (food, general goods and health care) and is only accessible year-round by rail (as all-season roads are not yet operational).…”
Section: Methodsmentioning
confidence: 99%
“…Until 01 October, 2016, in northern Ontario there were 32 fly-in communities and only eight fully eligible communities, 23 although all were desperately in need of the food subsidy. 6 The program came under serious criticism in the Auditor General's report in 2014 24 , which found that community eligibility was not based on need and Indigenous and Northern Affairs Canada had not verified whether the NNC subsidy was passed onto consumers in full. Following the election of the Liberal government in fall of 2015, another 37 communities were made eligible for the NNC subsidy after October 1, 2016; 19 of these new communities are located in northern Ontario.…”
Section: Historical Contextmentioning
confidence: 99%
“…La con tribution est directement versée aux détail lants enregistrés, qui ont la responsabilité de faire profiter leurs clients des économies ainsi réalisées, mais qui ne font l'objet d'à peu près aucun contrôle. Jusqu'au 1 er octo bre 2016, le nord de l'Ontario comptait 32 collectivités acces sibles uniquement par avion, dont 8 seulement avaient droit à une contribution complète 23 alors que toutes avaient désespérément besoin de cette con tribution pour l'alimentation 6 .…”
Section: Contexte Historiqueunclassified
“…Entre autres, le fait de regrouper les régions nordiques des pro vinces et le Grand Nord (Territoires du NordOuest, Yukon et Nunavut) empêche de saisir les contextes et les difficultés spécifiques en matière de commerce de détail alimentaire dans ces milieux. Un examen approfondi de l'environnement de vente au détail dans le nord des provinces a notamment révélé que l'absence de con currence et de choix dans le marché de détail et la longueur extrême des chaînes pour certains aliments) a mis en lumière un prix élevé des aliments 6 . Les mouvements et les organisations autochtones populaires ont réagi aux modi fications du programme de subvention en portant à l'attention du grand public cana dien les taux extrêmement élevés d'insé curité alimentaire dans le Nord canadien, grâce à des campagnes dans les médias sociaux et par des pages Facebook comme « Feeding My Family » 7 .…”
Section: Introductionunclassified
“…Foods are frequently sold past their best-before dates, show visible signs of mould, have been refrozen or have damaged packaging. 6 The CoP and RMT discussed how to assess food quality. One option was to take photographs from a select list of foods and assess them according to a four-point "quality" scale, designed by the RMT from literature sources and including packaging, labeling, temperature and freshness (see Table 1).…”
Section: Measuring Food Qualitymentioning
confidence: 99%